Prenatal diagnosis of a familial normal euchromatic variant of dup(15)(q11.2q11.2) in a pregnancy with a favorable outcome - Chih-Ping Chen; Tsang-Ming Ko; Jian-Pei Huang; Schu-Rern Chern; Peih-Shan Wu; Shin-Wen Chen; Fang-Tzu Wu; Wen-Lin Chen; Meng-Shan Lee; Wayseen Wang (Taiwanese Journal of Obstetrics & Gynecology, 2020)
Objective: We present prenatal diagnosis of a familial normal euchromatic variant of dup(15)(q11.2q11.2) in a pregnancy with a favorable outcome. Case report: A 32-year-old woman underwent elective amniocentesis at 17 weeks of gestation because of anxiety. Amniocentesis revealed a karyotype of 46,XX,dup(15)(q11.2q11.2). Simultaneous array comparative genomic hybridization (aCGH) analysis on the DNA extracted from uncultured amniocytes revealed the result of arr (1–22, X) × 2 with no genomic imbalance. Cytogenetic analysis of the parental bloods showed that the mother had a karyotype of 46,XX,dup(15)(q11.2q11.2), and the father had a karyotype of 46,XY. Prenatal ultrasound findings were unremarkable. A healthy 2948 g female baby was delivered at 39 weeks of gestation without any phenotypic abnormality. Cytogenetic analysis of the cord blood revealed a karyotype of 46,XX,dup(15)(q11.2q11.2). Conclusion: Prenatal diagnosis of dup(15)(q11.2q11.2) should include a differential diagnosis of a 15q11.2 (BP1-BP2) microduplication encompassing TUBGCP5, CYFIP1, NIPA2 and NIPA1, and aCGH analysis is useful for the differential diagnosis under such a circumstance.